2020
DOI: 10.1186/s12906-020-02912-9
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicine use in Timor-Leste

Abstract: Background: Traditional medicine use is common amongst peoples in developing nations. Timor-Leste is no exception. However little is known about the prevalence, pattern, satisfaction with, cost or type of traditional medicine used in Timor-Leste. This study aims to describe the prevalence, nature and basic demographic factors associated with contemporary traditional medicine use in Timor-Leste. Methods: A structured interview questionnaire was administered in Tetun to 50 surgical patients, 50 internal medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In addition, the population in rural areas of Timor-Leste is reluctant to utilize the health-care system because of various reasons, such as lack of patient transport, out-of-pocket expenses for hospital visits, cultural belief, and geographical barriers [ 16 , 33 ] and prefers instead to use traditional healers. [ 15 ] Often patients present very late after the burn injuries and already have complications. Other studies have reported that less than half of burn patients utilize hospital care and only about 5% of those need further care and require admission to an acute care facility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the population in rural areas of Timor-Leste is reluctant to utilize the health-care system because of various reasons, such as lack of patient transport, out-of-pocket expenses for hospital visits, cultural belief, and geographical barriers [ 16 , 33 ] and prefers instead to use traditional healers. [ 15 ] Often patients present very late after the burn injuries and already have complications. Other studies have reported that less than half of burn patients utilize hospital care and only about 5% of those need further care and require admission to an acute care facility.…”
Section: Discussionmentioning
confidence: 99%
“…The government provides free public healthcare, however mountainous terrain combined with cultural-, and socio-economical barriers make it challenging for the population to access medical services within an appropriate time frame. [ 15 17 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread use of traditional medicine is reported globally in both Western and Asian countries with varying local prevalence which ranges from 11% up to 60% of the studied population. [18][19][20][21] There is not much conclusive data available regarding the use of natural products in nicotine use disorders, but they may play an equally important role as a potential pharmacological agent for cessation of smoking. In fact, a considerably great amount of research has been conducted on the effects of natural products in nicotine use disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The factors affecting the use of TCM are various. Sociodemographic factors, income level, type and severity of the disease, dissatisfaction with modern medicine, limited health care access, cultural beliefs, long-term use of TCM methods, perceived usefulness and safety of these methods, accessibility of TCM methods and being affected by social networks are considered among the reasons why TCM methods are preferred 4,6,7,8,12 . In the literature, the main reasons that keep individuals from using these methods are reported as lack of scientific evidence for TCM methods, disbelief in their effectiveness and safety, and not performing the applications under hygienic conditions 7 .…”
Section: Introductionmentioning
confidence: 99%